MIN 23 Aceh Besar لترقية سيطرة التلاميذ على المفردات بــــ Card Sort استخدام وسيلة (لســـانـنــا (LISANUNA): Jurnal Ilmu Bahasa Arab dan Pembelajarannya, 2021)
The problem found by researcher in class V (B) MIN 23 Aceh Besar is that students are less interested in learning Arabic and make students not active in learning, so mastery in the vocabulary is low, as well the teacher does not use varied media in the learning process. Because of that the researcher tries to overcome these problems with applying cards sort media to improve students’ ability is mastering the vocabulary. The purposes of this research are to identify the effectiveness and student’s responses the application of card sort media to improve ability in mastering the vocabulary. The research method used by researcher is a pre experiment with “one group pre-test and post-test” design, and for data collection, the research used test and questionnaire. The researcher used percentage to analyze student’s responses and the T test to obtain the value of effectiveness. The results of T test to show that the application of card sort media is effective to improve the ability of students in mastering the vocabulary. The result of (T-Test) (-6.077) and the level of significance (sig) which the results. (.000) obtained meaning smaller than the value of the provisions (0.000) < (0.05).  And  the result of questionnaire showed that the students’ responses to the vocabulary learning by using card sort media is at a high level of 3,67.
Keywords: Media Card Sort; Vocabulary